1993
DOI: 10.1079/bjn19930125
|View full text |Cite
|
Sign up to set email alerts
|

Rape-seed meal toxicity in gnotobiotic rats: influence of a whole human faecal flora or single human strains ofEscherichia coliandBacteroides vulgatus

Abstract: Gnotohiotic growing rats harbouring either a whole human faecal flora or single human strains of Escherichia coli (EMO) or Bactevoides vulgatus (BVSHl) were fed for 7 weeks on semi-synthetic diets in which the protein source was either soya-bean meal (SM) or rape-seed meal (RM). For each bacterial status the RM-diet group was compared with the control group fed on the S M diet. The association of human faecal flora with the R M diet was responsible for reduced feed intake and reduced weight gain, an enlargemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 23 publications
(29 reference statements)
2
46
0
Order By: Relevance
“…However, the breakdown of GSL by microflora is likely to be more complex than hydrolysis performed by the plant myrosinases. Experiments with gnotobiotic animals support the hypothesis that bacteria yield specific toxic GSL derivatives (Rabot et al 1993 a). Further conversion of several GSL derivatives into unknown compounds has been demonstrated in sheep rumen fluid in vitro (Lanzani et al 1974;Duncan & Milne, 1992).…”
Section: Bacterial Metabolism Of Glucosinolatessupporting
confidence: 57%
See 1 more Smart Citation
“…However, the breakdown of GSL by microflora is likely to be more complex than hydrolysis performed by the plant myrosinases. Experiments with gnotobiotic animals support the hypothesis that bacteria yield specific toxic GSL derivatives (Rabot et al 1993 a). Further conversion of several GSL derivatives into unknown compounds has been demonstrated in sheep rumen fluid in vitro (Lanzani et al 1974;Duncan & Milne, 1992).…”
Section: Bacterial Metabolism Of Glucosinolatessupporting
confidence: 57%
“…Those performed in our laboratory suggest that the different toxic patterns usually observed in different animal species are more likely to be due to differences in the autochthonous digestive microflora than to intrinsic host sensitivity toward GSL. Indeed, when given a diet based on rapeseed meal, conventional rats exhibit GSL-linked symptoms different from those of gnotobiotic rats harbouring either chicken or human microflora (Nugon-Baudon et al 1988;Rabot et al 1993~). The inoculation of germ free rats with single strains of fowl or human origin provided further information about the role of intestinal microflora in the production of toxic GSL derivatives.…”
Section: Toxicity Of Glucosinolates a N D Glucosinolate Derivativesmentioning
confidence: 99%
“…The difference in composition of diets used, may have resulted in difference in the composition of gut microbes that hydrolyzes GLS and therefore in difference in the severity of toxicity of GLS degradation products (Woyengo et al, 2011). Also, Rabot et al (1993) found that toxic effects of dietary GLS are partly dependent on the composition of gut microorganism.…”
Section: Discussionmentioning
confidence: 99%
“…After 2 weeks adaptation to the diet and the £ora, two rats were killed by CO 2 inhalation and the levels of bacterial population in the stomach, small intestine, caecum and colon were determined by anaerobically growing serial 10-fold dilutions of the contents [6]. The other rats were randomly allocated to seven groups of four animals each and dosed by stomach tube under light ether anaesthesia, either with 50 Wmol sinigrin dissolved in 0.5 ml distilled water (six treated groups), or with 0.5 ml distilled water alone (one control group).…”
Section: Experimental Designmentioning
confidence: 99%